Pengelolaan limbah kulit jagung sebagai upaya pelestarian lingkungan - Azzahro, Sabrina (Maliki Interdisciplinary Journal, 2024)
Garbage is the biggest environmental problem that almost all countries experience. Every year the amount of waste generated by the population is increasing. Nearly 40% of waste sources are generated in household waste. In this case, good and proper waste management is needed so that it has many benefits. Waste management efforts must be carried out systematically, thoroughly and continuously. One of the household waste that is rarely used is corn husks. As a staple food in Indonesia, corn can produce approximately 1 ton of corn husks every day. Therefore, proper management is needed so that it has a selling value and can improve the economy. One of the corn husk waste processing products is compost.